Pengelolaan Pengaduan Masyarakat Melalui Layanan Aspirasi dan Pengaduan Online Rakyat (LAPOR!) Pada Dinas Komunikasi dan Informatika Kota Samarinda - Naila Hayati Azzaki; Bambang Irawan (Majalah Ilmiah Dinamika Administrasi (MIDA), 2026)
The Communication and Informatics Office Of Samarinda City plays a role in managing public complaints online through the LAPOR! application, which aims to relize transparent, accountable, and responsive public services. This Study aims to describe how the management of public complaints through LAPOR! is carried out based on the POAC functions (Planning, Organizing, Actuating, and Controlling), as well as to identify the inhibiting factors in the complaint management process. This research uses a qualitative method with a descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation, with informants from the Communication and Informatics Office, relevant Regional Government Organizations (OPD), and LAPOR! users. The data were analyzed using the interactive model of Miles & Huberman. The results of study show that the management of public complaints through LAPOR! has been carried out quite well, starting from program planning, resource organizing, service implementation, to periodic supervision and evaluation. However, there are still obstaclessuch as limited human resources, suboptimal internal coordination among OPDs in following up on complaints, and technical issues.